Evaluasi Program Regrouping Sekolah Dasar Negeri - Erowati, Maria Tri; Slameto, Slameto; Wasitohadi, Wasitohadi (Kelola: Jurnal Manajemen Pendidikan, 2018)
This research is an evaluation that aimed to know the process of implementation policy, factors that effected regrouping school program, the effects of regrouping, and how the effectiveness and efficiency of the regrouping program in SD Negeri Tukang 01 and 02, Pabelan, Semarang. This evaluation research used goal-free evaluation with the subject is SD Negeri Tukang 01 and 02 Pabelan. The collecting data used interview, observation, and documentation, then the data analysis was data reduction, data presentation, and drawing the conclusion. The result of this research showed that SD Negeri Tukang 01 and 02 already grouped for 4 years before the Regent's letter published. Then, the students, teachers, government’s rule, and school condition be the factors affected the regrouping program. This regrouping program has several impacts, they answered the teacher need and/or there was a teacher mutation. Then for students, there weren’t much effect because the students already friends, and then increasing the school’s facility. Besides that, regrouping program might increase school quality and the society would not be confused to choose the school for their child. But then, the alumni of these school can be difficult to get legalize for their certificate. This regrouping program is effective and efficient enough to do because the teacher problem can be solved, then the school facility can be maximized and about the budgeting organize by the main school.